Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE Monday. Living-room ; preparation for wash. Tuesday. Washing. Wednesday. Bedrooms. Thursday. Bathroom, lavatory, stairs, pantry, larder, and cupboards. Friday. Kitchen and scullery Saturday. Landing, hall, stairs, all lighting fittings (electric lamps, etc.), yard, steps, preparation for Sunday. ON CLEANING Living-room. — Note: Fire to be done before all else. (This applies to bedrooms also.) If weekly clean: remove and dust all ornaments and movable bits of furniture; cover rest with dust sheets; take down pictures; roll up curtains, etc.; sweep carpet (see directions p. 6), dust and polish surrounds, dust room; wash ornaments; dust and polish furniture; wipe down pictures; replace. If daily clean: fire; carpet; floor; dust. Bedroom. — Ornaments, etc., as living-room if weekly clean, but first — air bed; empty slops; make bed; cover up all movable furniture with dust sheet; carpet — as living-room. (For note on polished floors, see p. 14.) Daily clean: air bed; empty slops; make bed; carpet; floor; dust. Kitchen and Scullery. — Remove all china, pots, pans, etc.; sweep and dust; scrub shelves with soapy water ; when dry put on clean paper, if needed, and then replace pans and china ; give sink a special good cleansing, and swill by turning on cold tap. Pantry and Store Cupboard. — (a) Remove all china and wash; sweep and dust; scrub floor and shelves, and when dry replace china. (b) Remove food ; scrub as above, and then, if necessary, put on clean paper when dry. Page Four 177/5/8/1